The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.20452/pamw.2778
|View full text |Cite
|
Sign up to set email alerts
|

Results of an open-access lung cancer screening program with low-dose computed tomography: the Gdańsk experience

Abstract: INTRODUCTION Lung cancer screening with low-dose computed tomography (LDCT) is one of the most promising tools for reducing mortality from lung cancer. OBjeCTIves The aim of the study was to evaluate the results of an open-access lung cancer screening program with LDCT. PATIeNTs AND meThODs In total, 8649 asymptomatic volunteers between 50 and 75 years of age with a smoking history of at least 20 pack-years underwent LDCT screening. The presence of lung nodules with a diameter of less than 5 mm required a foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…We looked for JAK/STAT pathway molecules whose modified immunoexpression could have diagnostic or prognostic value in lung cancer and would support clinicians in their daily practice. 23,24 Our results confirmed the increased levels of STATs, namely pSTAT3, pSTAT5, and pSTAT6, in NSCLC specimens and suggested their importance in lung carcinogenesis. The simultaneous overexpression of proteins was observed in nearly 70% of tumor samples and was similarly high, regardless of the NSCLC histotype (SCC or NSCC).…”
supporting
confidence: 77%
“…We looked for JAK/STAT pathway molecules whose modified immunoexpression could have diagnostic or prognostic value in lung cancer and would support clinicians in their daily practice. 23,24 Our results confirmed the increased levels of STATs, namely pSTAT3, pSTAT5, and pSTAT6, in NSCLC specimens and suggested their importance in lung carcinogenesis. The simultaneous overexpression of proteins was observed in nearly 70% of tumor samples and was similarly high, regardless of the NSCLC histotype (SCC or NSCC).…”
supporting
confidence: 77%
“…In our own experience, around 75% of patients with screening-detected lung abnormalities underwent unnecessary diagnostic work-up, including around 25% of patients subjected to further invasive procedures (Rzyman et al, 2013). For these reasons, complementation of CT-based screening with other tests allowing effective and reliable preselection of individuals for LD-CT examination, or better discrimination between benign and malignant nodules detected by LD-CT, seems a critical issue for practical application of this strategy (Priola et al, 2013;Rzyman et al, 2015). Blood is the most available source of biomarkers potentially enhancing the power of early lung cancer detection or differentiating lung nodules.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer in stage I was 64 to 70% of detected cancers. The results of these studies have highlighted the scale of tobacco smoking in the Polish population, indicated the growing awareness of the risk of lung cancer in the society and confirmed the efficacy of LDCT in detecting pulmonary nodules [39,40].…”
Section: Screening In the United States Europe And Polandmentioning
confidence: 62%